Design And Performance Verification Of A Booster Fan Installation At The Red Lake Mine - E. DeSouza; P. Rocque; L. Sletmoen (Society for Mining, Metallurgy & Exploration, 2003)
Plans for achieving planned production rates at the Red Lake Mine High Grade Ore Zone required that the mine ventilation system be upgraded. Time constraints required that only a site assessment of the mine ventilation system be performed followed by recommendations for providing adequate ventilation conditions at the production zone. This paper describes the engineering assessment, design and commissioning of the ventilation system upgrade for achieving increased flows at the high grade ore zone. The work was successfully achieved with minimal capital expenditures and disruption to the mining cycle.